The lambda calculus : its syntax and semantics - Barendregt, H. P. (Hendrik Pieter) (Studies in logic and the foundations of mathematics ;, 1984)
The revised edition contains a new chapter which provides an elegant description of the semantics. The various classes of lambda calculus models are described in a uniform manner. Some didactical improvements have been made to this edition. An example of a simple model is given and then the general theory (of categorical models) is developed. Indications are given of those parts of the book which can be used to form a coherent course.